Pesan Pemberitaan Prabowo Subianto Dalam Pemilu 2024 - Abdurrohman, Haidar; Nani Nurani Muksin (Jurnal Pewarta Indonesia, 2025)
The study aims to analyse the message content of Prabowo Subianto's news coverage. Prabowo Subianto's news coverage was chosen because news coverage often has biased political language. Message content analysis was conducted so that readers can receive the message that the media actually wanted to convey regarding Prabowo Subianto as the presidential candidate for Indonesia's Replubik for the 2024 to 2029 period. This analysis compared two online media, namely Kompas.com and Tempo.com. These two media outlets were chosen because they were able to compare media outlets that were biased towards the object of the news, namely Prabowo Subianto. One of the media is considered to have partiality. Content analysis can show whether a news story is positive or negative towards the object of the news that will be conveyed to the audience. From this analysis, it was found that Kompas.com often reported Prabowo Subianto in its news portal, and the tendency of its news content to give a positive message. Tempo.com news portal did not cover Prabowo as often, and the news tended to be neutral and sometimes provided criticism, giving a negative impact on Prabowo Subianto. As a result of the analysis, it is hoped that Indonesian online media should be more in favour of the public in reporting the truth, so that the Indonesian people will not choose the wrong president for the next 5 years. This research is still limited to two media outlets and has not analysed the other media outlets.